The Role of Relationship Marketing in Improving an Organization's Mental Image (A Field Study in Insurance Companies in Latakia Governorate) - بلدية, إياد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research sought to examine the relationship between relationship marketing on the one hand, and between organization's mental image in Insurance companieson on the other hand, where the researcher distributed a questionnaire to a sample of the employees reached (130) questionnaire, since that (118) responses were received, and (110) questionnaire were used in the analysis. To test the relationship, the researcher used the Student T test for one sample, as well as the Pearson correlation coefficient. The research concluded that there is a decrease in the level each of internal marketing, continuous quality improvement, and attention to customer complaints in companies under study, as well as a decrease in the level mental image in companies under study. The research concluded that there is significant relationship between relationship marketing and mental imageininsurance companies, and thus the existence of the role of relationship marketingin improving of mental image. The research presented a set of recommendations and proposals related to continuous improvement of product quality and attention to customer complaints